Efficacy of the "pick and roll" offense in top level European basketball teams - Marmarinos, C.; Apostolidis, N.; Kostopoulos, N.; Apostolidis, A. (Journal of Human Kinetics, 2016)
Team offense in basketball games consists of a set of offensive actions carried out with the cooperation of two or more players. Of these actions, the most commonly used in the last decade is the on-ball screen called the "pick and roll." The aim of this study was to analyze all of the pick and rolls conducted in the Euroleague championship from all of the 24 participating teams and to investigate the possible relationships between success in the pick and roll and overall success of the teams. For this purpose, 12,376 pick and rolls from 502 matches were analyzed and classified in categories according to the end result of the offensive possession. The results showed that the most effective type of pick and roll offense was when a shot was attempted after 2 passes from the pick and roll occurrence, followed by the screener`s shot when he rolled to the basket. Additionally, linear regression analysis confirmed that pick and roll effectiveness could predict the final classification of the teams. Conclusively, coaches of the high level European clubs should focus on training the players to the most efficient phases of the pick and roll offense, so that the chances of winning the championship to be maximized.